(untitled) (Jurnal Ipteks Terapan, 2023)
The purpose of this research is to determine and analyze the influence of Earning Per Share (EPS), Price to book value (PBV), Debt to Equity Ratio (DER), Dividend Payout Ratio (DPR) and Working Capital on share prices in manufacturing sector companies. Pharmaceutical Industry on the Indonesian Stock Exchange in the 2017-2022 period. This type of research is quantitative research, namely research oriented towards processing data in the form of numbers contained in financial reports. The population in the research is manufacturing companies in the Pharmaceutical Industry sector on the Indonesian Stock Exchange on period 2017-2022. The sample used in study This as many as 7 Pharmaceutical company. The data analysis technique uses descriptive analysis and multiple linear regression analysis using SPSS version 26 software. Based on the results Partial research shows that Earning Per Share (EPS) has a positive and significant effect on Stock Prices, Price to Book Value (PBV) has a positive but not significant effect on Stock Prices, Dividend Payout Ratio (DPR) has a positive and significant effect on Stock Prices, Capital Work (MK) has a positive and significant effect on share prices, and simultaneously Price to Book Value (PBV), Earnings Per Share (EPS), Debt to Equity Ratio (DER), Dividend Payout Ratio (DPR) and Working Capital (MK) has a significant effect on stock prices in the pharmaceutical sector in Indonesia. Halal labeling has a positive and significant effect on purchase decisions , Simultaneously, the Halal Awareness and Halal Labeling variables have a significant effect on the purchase decisions of customers using the Online Food Delivery service . And based on the coefficient of determination the dependent variable is able to influence the dependent variable by 48.1%